Diagnostics of Creativity as the Initial Stage of its Formation of Students of Humanitarian Specialties - Osobov, Ivan (Pedagogical Discourse, 2013)
The article focuses attention on the diagnostics level of formation of creativity in students of humanitarian specialties in university teaching. The author shows the creative tasks that are formulated based on the outcome of the testing. The role of information and communication technologies as a way to stimulate creativity is substantiated. The author analyzes the possibility of introducing in the educational process of high school special course creative training.